Cost Deployment: um estudo abordando a contribuição da ferramenta estratégica na gestão dos custos de perdas em uma empresa do Polo Industrial de Manaus - Paixão, Lucas Lopes (Brasil, 2024)
In the contemporary business context, efficient cost management is essential for the competitiveness of organizations. This study investigated the role of Cost Deployment as a strategic tool for identifying and managing costs associated with losses and waste in a multinational automotive company located in the Manaus Industrial Complex. The research used an empirical case study approach with mixed methods, combining qualitative and quantitative analyses of the company's operational and financial data. Cost Deployment was explored as a methodology derived from World Class Manufacturing (WCM), focusing on the systematic reduction of losses and waste by attributing costs to identified root causes. The results revealed that the implementation of Cost Deployment allowed a detailed analysis of production losses, categorized and quantified through specific matrices, which facilitated the prioritization of improvements in the impacted areas. This study contributed to the theoretical and practical understanding of cost management, highlighting the importance of the strategic approach of Cost Deployment for organizational efficiency and competitiveness.